The usage font of Braille for medicine package protection - Васильченко, Владимир Сергеевич; Бизюк, Андрей Валериевич; Бизюк, Ирина Григорьевна (Eastern-European Journal of Enterprise Technologies, 2012)
In this article the problem of Braille code verification was investigated in order to use code inscriptions to protect medical packaging. In the study an algorithm to recognize Braille was designed, with the ability to play aloud the text information by software tools. The developed method uses the principle of three-dimensional images scanning named "shape from the shadows"; image processing using Photoshop or analog; code identification by the programs of OCR class and playing text information aloud by means of software. Also the principle of data encryption using Braille was developed and new methods of packaging protection with Braille were offered. Received test results demonstrate that the investigated technique can be used as the basis for a set of software and hardware for a new way to protect medical packaging with Braille